Farmers’ Adaptation Strategies to Rainfall Variability in Oljoro-Orok Ward, Kenya - Karanja, Amon Mwangi (Annals of Arid Zone, 2021)
The paper analyzed farmers’ adaptation strategies to rainfall variability in Oljoro-orok Ward in Nyandarua County, Kenya. The major crop grown in Oljoro-orok Ward is Irish potatoes. Stratified proportionate random sampling was used to select 192 respondents from different locations in the Ward. Data was analyzed using descriptive statistics where multiple responses on the adaptation measures were accommodated in the final analyses. It was found that crop diversification was the most common adaptation measure practiced in the ward (38%) followed by timely planting (30%), off season approach (24%) and irrigation (8%). Farmers practiced crop diversification where they planted other crops such as animal feeds and vegetables such as onions and carrots that mature faster in times of unfavorable rainfall. The Ministry of agriculture and County government of Nyandarua should create more avenues to reach out to all farmers and educate them on the importance of adopting scientific practices to increase Irish potato production in light of rainfall variability in Oljoro-orok ward. Kenya Agriculture and Livestock Research Organization should make hybrid potato seeds accessible and affordable to all farmers in Oljoro-orok Ward. The Kenya Meteorological Department should enhance relay of seasonal weather forecast to reach more farmers within a short period at the beginning of every season to allow timely planting.Key word: Adaptation strategy, crop diversification, rainfall variability.